2019
DOI: 10.1111/dth.13100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of family constellation seminars on itch in patients with atopic dermatitis and psoriasis: A patient preference controlled trial

Abstract: Family dynamics play a major role in itch related dermatoses. The aim of the study was to evaluate the effectiveness of family constellation seminars (FCS) in the decrease of itch in atopic dermatitis (AD) and psoriasis. Thirty‐one adult patients with chronic itch (16 with AD and 15 with psoriasis) were allocated to intervention group (FCS + G) and control group (CG). Patients from FCS + G have participated in a series of four FCS for 3 months. During the study period, all patients used only emollients. Itch w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…Family constellation seminars method was not discussed in several reviews about psychological interventions in the patients with itch (52-56), but we reported its effectiveness in decreasing itch, scratch, and improving skin condition (51). After a series of FCS, along with reduced itch severity and duration, patients with AD and psoriasis improved attentiveness, working capacity, productivity, quality of sleep and daily activities, and felt less emotional depletion due to itch (51).…”
Section: Family Constellation Seminars As a Candidate Methods For Pat...mentioning
confidence: 85%
“…Family constellation seminars method was not discussed in several reviews about psychological interventions in the patients with itch (52-56), but we reported its effectiveness in decreasing itch, scratch, and improving skin condition (51). After a series of FCS, along with reduced itch severity and duration, patients with AD and psoriasis improved attentiveness, working capacity, productivity, quality of sleep and daily activities, and felt less emotional depletion due to itch (51).…”
Section: Family Constellation Seminars As a Candidate Methods For Pat...mentioning
confidence: 85%
“…From our standpoint, thanks to several important controversies and criticisms (e.g., Goldner, 2003; Haas, 2005, 2009; Keupp, 2003; Talarczyk, 2011; Thielbörger, 2014), and despite the lack of more rigorous research (Alonso, 2005; Sparrer & von Kibed, 2008), there are slowly emerging indications that, as an evidence-based psychotherapy (Berg, 2019, 2020; David & Montgomery, 2011; Lee & Hunsley, 2015), FC is effective (Franke, 2003b; Ramos & Ramos, 2019; Wolynn, 2005), efficacious (Höppner, 2006; Hunger, Bornhäuser, et al, 2014; Hunger, Weinhold, et al, 2014; Jafferany et al, 2019; Weinhold et al, 2013), and efficient (Ramos & Ramos, 2019). Thus, FC is still a psychotherapy in search for an identity (Alonso, 2005), scientificity, and a more comprehensive understanding.…”
Section: Family Constellationsmentioning
confidence: 99%
“…Finally, psychosocial interventions such as family constellation seminars examining transgenerational family dynamic patterns have been shown to reduce itch in psoriatic patients (Jafferany et al, 2019).…”
Section: Psychosocial Comorbidities Of Psoriasis and Itchmentioning
confidence: 99%